Land use transition and its driving mechanisms in China’s human-elephant conflict areas - WANG Yuan, WANG Yahui, YANG Aoxi, FAN Hui, XIE Fei (Ziyuan Kexue)
[Objective] In the context of increasing conflicts between humans and Asian elephants, this study aims to elucidate the characteristics and driving mechanisms of land use transition in conflict areas and explore the mutual feedback relationship between land use transition and human-elephant conflicts. [Methods] This study focuses on the human-elephant conflict areas in Pu’er City and Xishuangbanna Prefecture in Yunnan Province as the study areas, based on four periods of remote sensing images in 1990, 2000, 2010, and 2020, as well as two periods of household questionnaire survey data in 2020 and 2022, utilizing spatial analysis and input-output analysis methods to reveal the characteristics and driving mechanisms of land use transition in human-elephant conflict zones. [Results] (1) Land use transition in regions inhabited by Asian elephants is significant, with forest areas experiencing a decrease followed by a slow recovery, accompanied by a decrease in orchard area. In the core conflict areas, a multi-crop structure dominated by rubber has formed (accounting for 69.8% of the planting area). (2) Land use in the core conflict zone exhibits relatively extensive patterns, with land transfer rates and input-output efficiency demonstrating significantly lower values compared to those observed in peripheral regions. (3) Land use transition is influenced by multiple factors, including Asian elephant activities, economic development, and agricultural policy adjustments. The frequent crop destructions of by Asian elephants is the most direct factor for land use transformation in the study area. [Conclusion] With the intensification of human activities and the increase in the population of Asian elephants, onflicts will become more severe in the future. The “human-elephant” conflict and land use transformation are closely interrelated and mutually reinforcing, and land use transformation may alleviate the conflict between humans and elephants. Relevant departments should guide Asian elephants to return to their habitats, optimize regional production and ecological space, reduce human-elephant conflicts, and promote the sustainable development of local social, economic, and ecological.